2019
DOI: 10.1177/2150135119876600
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine as an Adjunct for Refractory Junctional Ectopic Tachycardia Following Pediatric Cardiac Surgery: A Preliminary Study

Abstract: Objectives: Junctional ectopic tachycardia (JET) is a relatively common narrow complex rhythm typically characterized by atrioventricular dissociation or retrograde atrial conduction in a 1:1 pattern. Junctional ectopic tachycardia can be a life-threatening disorder, causing severe hemodynamic compromise and increased morbidity and mortality. The treatment of refractory JET can be very difficult, even with multimodal therapeutic interventions. The purpose of this study was to assess the role of ivabradine in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In fact, the study is limited by (1) the small number of patients, (2) the short duration of follow-up, and (3) the lack of adequate assessment of ivabradine efficacy since it wasn't used as a single treatment in any of the patients. Furthermore, two retrospective studies, published in 2019, have tackled the use of ivabradine in treating post-operative pediatric JET (27,28). First, Krishna et al reported an adequate response to ivabradine in a cohort of eight patients with JET acquired after open-heart surgery.…”
Section: Ivabradine and Junctional Ectopic Tachycardiamentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the study is limited by (1) the small number of patients, (2) the short duration of follow-up, and (3) the lack of adequate assessment of ivabradine efficacy since it wasn't used as a single treatment in any of the patients. Furthermore, two retrospective studies, published in 2019, have tackled the use of ivabradine in treating post-operative pediatric JET (27,28). First, Krishna et al reported an adequate response to ivabradine in a cohort of eight patients with JET acquired after open-heart surgery.…”
Section: Ivabradine and Junctional Ectopic Tachycardiamentioning
confidence: 99%
“…Furthermore, two retrospective studies, published in 2019, have tackled the use of ivabradine in treating post-operative pediatric JET ( 27 , 28 ). First, Krishna et al reported an adequate response to ivabradine in a cohort of eight patients with JET acquired after open-heart surgery.…”
Section: What Is Known About Ivabradinementioning
confidence: 99%
See 1 more Smart Citation
“…Thelatest tool in the armamentarium is ivabradine. [ 83 84 85 ] Ivabradine is recommended for select adults with chronic stable angina, heart failure, and inappropriate sinus tachycardia. Ivabradine acts through HCN channels which may play an important role in etiopathogenesis.…”
Section: Managementmentioning
confidence: 99%
“…[ 86 ] In small case series, ivabradine has been found to be effective as an adjunct to amiodarone and as the sole agent. [ 83 84 85 ] Rate control is the initial response, followed by conversion to sinus rhythm. [ 84 ] Early administration before hemodynamic compromise ensues will be key as absorption will be affected once cardiac output is compromised.…”
Section: Managementmentioning
confidence: 99%